Investigation of flow structure and heat exchange formation in corrugated pipes at transient reynolds numbers - Bascova, Oleksandra; Voropaiev, Gennadii (Eastern-European Journal of Enterprise Technologies, 2017)
The problem of convective heat transfer in the initial section of a pipe with a corrugated section was considered at transient Reynolds numbers. Influence on the intensity of heat exchange and the magnitude of hydraulic resistance of geometric parameters (wavelength and amplitude) of the corrugated insert, variability of the thermophysical properties of the heat carrier and the direction of the heat flow was estimated. Threshold value of the corrugation wavelength (L/R0>0.6) was determined for the Reynolds number range under consideration for which there was a significant growth of heat exchange. Influence of the gradient of the dynamic viscosity coefficient on flow stability and intensification of heat exchange in internal flows was demonstrated. Influence of Reynolds and Prandtl numbers on local heat transfer, hydraulic resistance and flow structure was determined. It was established that the use of corrugated surfaces is ineffective at Reynolds numbers less than 2000. It was shown that heat exchange in a pipe can be raised to 30 % with an increase in hydraulic resistance of 1.05 times in the range of Reynolds numbers 2·103...1.4·104 with the use of a nonencumbering corrugation.